Method optimisation and application based on solid phase extraction of non steroidal anti-inflammatory drugs, antiretroviral drugs, and a lipid regulator from coastal areas of Durban, South Africa - Sisonke Sigonya; Stanley Chibuzor Onwubu; Phumlani Selby Mdluli; Thabang Hendrica Mokhothu (SN Applied Sciences, 2022)
Highlights The Solid Phase Extraction method is optimised for the pre-concentration of pharmaceuticals in coastal waters. Non-steroid anti-inflammatory drugs and Antiretroviral drugs are successfully quantified in coastal waters. The concentration of pharmaceuticals detected in coastal waters varies with each season.